Acute effect of static stretching on muscle force in older women - André Luiz Demantova Gurjão; Nelson Hilário Carneiro; Raquel Gonçalves; Rodrigo Ferreira de Moura; Sebastião Gobbi (Universidade Federal de Santa Catarina, 2010)
The objective of this study was to investigate the acute effect of static stretching on the peak rate of force development (PRFD) and maximum voluntary contraction (MVC) in older women. Ten women (68.5 ± 7.0 years; 70.9 ± 8.1 kg; 159.4 ± 6.0 cm; body mass index: 28.0 ± 3.8 kg/m2) were studied. MVC and PRFD were determined by leg press exercise before and after the control or stretching condition (three sets of 30 seconds of static stretching of the quadriceps) on two different days (interval of 24 hours). PRFD was determined as the steepest slope of the curve, calculated within regular windows of 20 milliseconds (∆force/∆time) for the first 200 milliseconds after the onset of contraction. MVC was determined as the highest value recorded in each set. Only one condition was tested on each day and the order of application of each condition was determined randomly. The stretching intensity was evaluated by the muscle pain threshold. Four post-condition assessments (post-treatment, 10, 20, and 30 minutes) were performed to monitor muscle strength. ANCOVA 2x5, followed by the Scheffé post-hoc test, showed no significant interactions between conditions vs. times (P > 0.05) for PRFD or MVC. In conclusion, acute bouts of static stretching of the quadriceps femoris do not affect the ability of rapid and maximum muscle force production in older women.